NONET AND SELZNICK’S RESPONSIVE LAW CONCEPT IN A HISTORICAL PHILOSOPHY PERSPECTIVE - Agam Ibnu Asa; Misnal Munir; Rr. Siti Murti Ningsih (Bagian Dasar-Dasar Ilmu Hukum Fakultas Hukum Universitas Diponegoro, 2021)
The responsive laws of Nonet and Selznick's thinking became one of the results of conceptual ideas about the laws that are elaborated periodically. The development of responsive law may be less comprehensive when it has not been found the historical fundamental aspects on which it is focused. It is thus important to study the concept of Nonet and Selznick's responsive legal philosophically. The method in this research is the philosophical method. The results of this study include: first, the development of law in Nonet and Selznick's view is divided into three periods of repressive law, autonomous law, and responsive law. Second, Nonet and Selznick's responsive law when reviewed in historical perspective gained an understanding that responsive law exists from a constantly creative legal subject by looking at legal issues and realities in an increasingly complex society, and responsive law is a law that has always served as part of cultural dynamics.